Corn Production Exploration of Central Sulawesi Using Multiplicative Winter Model - Putera, Fachruddin Hari Anggara; Amelia, Rezi; Handayani, Lilies (Parameter: Journal of Statistics, 2022)
Corn is a very important food ingredient after rice. Central Sulawesi corn production data is in the form of time series data which every year in certain months increases or decreases in production. Therefore, the method that can be used for forecasting is the winter multiplicative method. This study aims to build the best model for forecasting corn production in Central Sulawesi using the winter multiplicative method. The results of this study are used to explore corn production for the next period. Modeling is done by selecting the best combination of parameters and the best combination of model parameters is obtained with a mean absolute percentage error (MAPE) of 18% with a value of Î± = 0,5; Î³ = 0,1; and Î² = 0,1. The data plot of the forecasted corn production shows fluctuations which indicate seasonal factors and trends in it